The durability of concrete subject to mechanical load coupled with freeze–thaw cycles: a review - Xu, Yanqun; Ye, Hansong; Yuan, Qiang; Shi, Caijun; Gao, Yun; Fu, Qiang (Archives of Civil and Mechanical Engineering, 2022)
In cold regions, concrete structures are often subject to the coupled effect of mechanical loading with freeze–thaw (F–T) cycles, which results in a reduced service life. In this paper, the state of the art and challenges regarding the durability of concrete subjected to mechanical loading coupled with F–T cycles are reviewed in depth. The experimental setups used to simulate the coupled effect of mechanical loading with F–T cycles were summarized first, including the shapes of the specimens, operation methods, advantages, and limitations. Subsequently, relevant research methods such as numerical simulation methods and damage characterization methods were presented. Afterward, special attention was dedicated to the mechanism elaboration and performance improvement of the concrete subject to the coupled effect. Finally, some thoughts on potential directions for future work were discussed.